Educomunicação e cidadania: uma análise dos produtos comunicacionais do ministério público do Rio Grande do Sul nos seus aspectos educomunicacionais e cidadãos - Fernandes, Angela Carvalho (Universidade do Vale do Rio dos Sinos, 2024)
The research presented aims to promote a study on topics related to educommunication, citizenship and communication, carrying out an analysis of the communication products of the Public Ministry of Rio Grande do Sul (MPRS), to understand how it is viable to observe the presence of educommunicational aspects and citizens in these communication channels. Therefore, the study aims to elucidate how educommunication and citizen aspects bring information and knowledge to society, interpret the institution's communication products, propose improvements in educommunication processes and reflect on the impacts that educommunication and citizenship generate for society. Based on these reflections, it will be possible to answer the problem question that is being inserted in this dissertation: “How do MPRS communication products inform, educate, problematize, guide, question the understanding of citizenship exercises for subjects?”. The concepts of educommunication, citizenship, communication and communication products will be addressed throughout the research, with the aim of reflecting on these themes and questioning the aspects underlying this context. Furthermore, it is necessary to include a chapter that explains the role of the MPRS, in order to highlight the importance of this institution in society and enable readers to understand what its role is. Therefore, it is essential to describe and analyze the means of communication used by the MPRS, which will help readers better understand the details of this study. The theoretical framework is configured by arguments from: Soares, Kunsch, Felice, Sodré, Aristóteles, Duarte, Marshall, Alves, Soares, Edgar Morin, MCLuhan, Peruzzo and Baccega. The methodology was defined based on the strategies proposed by: Bachelard, Bonin, Bourdieu and Maldonado. It could be seen that educommunication and citizenship collaborate with society in the process of claiming their rights, and, therefore, the MPRS could improve the incorporation of these elements in its communicative production. After carrying out the exploratory research, it was found that the MPRS could improve its approach in relation to educommunicational issues present in its communication materials, which would contribute to helping society better understand its rights and duties within the scope of citizenship. The MPRS could develop greater intensity educommunication strategies, so that it builds a communication environment of great knowledge for society.
Keywords: Comunicação; Cidadania; Educomunicação; MPRS; Produtos comunicacionais; Communication; Citizenship; Educommunication; communication products; ACCNPQ::Ciências Sociais Aplicadas::Comunicação